2016
DOI: 10.1155/2016/5203898
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Infliximab Therapeutic Drug Monitoring among Patients with Inflammatory Bowel Disease and Concerns for Loss of Response: A Retrospective Analysis of a Real-World Experience

Abstract: Background. Infliximab (IFX) therapeutic drug monitoring (TDM) allows for objective decision making in patients with inflammatory bowel disease (IBD) and loss of response. Questions remain about whether IFX TDM improves outcomes. Methods. Patients with IBD who had IFX TDM due to concerns for loss of response were considered for inclusion. Serum IFX trough concentration and anti-drug antibody (ADA) concentrations were measured. Patients were grouped by TDM results: group 1, low IFX/high ADA; group 2, low IFX/lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…TDM resulted in treatment changes in 22% patients with Crohn's disease, and in 37% of inflammatory bowel disease patients with secondary loss of response. 13,14 Similar results have been seen in a pediatric inflammatory bowel disease cohort. 15 Although dose reduction has been shown to be a feasible approach, such a proactive empirical approach in patients showing a good response has rarely been employed.…”
Section: Dovepresssupporting
confidence: 77%
See 1 more Smart Citation
“…TDM resulted in treatment changes in 22% patients with Crohn's disease, and in 37% of inflammatory bowel disease patients with secondary loss of response. 13,14 Similar results have been seen in a pediatric inflammatory bowel disease cohort. 15 Although dose reduction has been shown to be a feasible approach, such a proactive empirical approach in patients showing a good response has rarely been employed.…”
Section: Dovepresssupporting
confidence: 77%
“…We identified an IFX trough level threshold around 2.8 mg/L for discriminating between future treatment failure and remission/low disease activity, in line with results for inflammatory bowel disease patients. 4,14,23 Accordingly, we adjusted our therapeutic ranges for IFX to 3-7 mg/L. Pouw et al found a correlation between disease activity and ADL trough levels, identifying a therapeutic window of 3-12 mg/L, while Keystone et al recommend a narrower interval, 5-8 mg/L.…”
Section: Infliximab Adalimumab and Etanerceptmentioning
confidence: 99%
“…The change in colour, from blue to yellow, was recorded using the spectrophotometry technique. The intensity of yellow colour was directly proportional to the concentration of the drug . A suboptimal infliximab serum level was defined as a level of less than 3.5 μg/mL.…”
Section: Methodsmentioning
confidence: 99%
“…The secondary loss of response could be related to the formation of antidrug antibodies (9)(10)(11)(12). Mitchell et al (2) concluded that immunogenicity to infliximab could occur in 11% of patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation